Concerning the transition to farming in the East Baltic - Antanaitis, Indre (Documenta Praehistorica, 1999)
The aims of this paper are three-fold: to reviw the current theory regardind the general, practical (animal and plant resource utilization) transition to farming; to draw attention to problems in the data base from whicht theoretical conclusions are made; and to explore specific, contextual socio-cultural changes that occured simultaneously during the practical transition, in particular those reflected in the changing forms of burials.
Keywords: archaeology; arheologija; arheološke najdbe; neolitik; Litva